Change of Direction Assessment Following Anterior Cruciate Ligament Reconstruction: A Review of Current Practice and Considerations to Enhance Practical Application - Joao Beleboni Marques (14152212) (2022)
Change of direction (CoD) has been indicated as a key mechanism in the occurrence of anterior cruciate ligament (ACL) injury during invasion sports. Despite these associations, assessments of knee function in athletic populations at the time of return to sport following ACL reconstruction (ACLr) have often focused on strength and single-leg hop tests, with a paucity of evidence to describe the CoD characteristics. Therefore, the aim of this narrative review was to describe the movement strategies exhibited following ACLr during CoD tasks and to critically analyze the range of tests that have been used. Specifically, we examined their ability to identify between-limb deficits and individuals who display a heightened risk of secondary injury and/or reductions in their level of pre-injury performance. MEDLINE, PubMed and SPORT Discuss databases were used and 13 articles were identified that met the inclusion criteria. Examination of the available literature indicates that current field-based practices are not representative of relevant sport demands and are unable to effectively assess knee function following ACLr. Laboratory-based studies have identified residual deficits and altered movement strategies at the time of return to sport, and this in part may be related to risk of re-injury. However, these assessments exhibit inherent limitations and are not practically viable for monitoring progress during rehabilitation. Consequently, alternative solutions that are more-aligned with the multitude of factors occurring during CoD maneuvers in chaotic sports environments are warranted to allow practitioners to ‘bridge the gap’ between the laboratory and the sports field/court. This approach may facilitate a more informed decision-making process with the end goal being, a heightened ‘return to performance’ and a lower risk of re-injury. Other Information Published in: Sports Medicine License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: http://dx.doi.org/10.1007/s40279-019-01189-4